2013
DOI: 10.7763/ijiet.2013.v3.306
|View full text |Cite
|
Sign up to set email alerts
|

Concept Map in Knowledge Sharing Model

Abstract: Abstract-Concept maps are widely used in education and business as a first step in knowledge sharing between the groups of people in communicate their complex idea and creativity. However, the mapping process is quite complex because all of the inherent ambiguity in aid creativity and ideation must be resolved to produce the facilitative tool for knowledge sharing model. This study has intended to show how concept map based knowledge models can be used as facilitator tools in create, locate and disseminate inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Concept maps, by putting individual mental models in the open, allow people to acknowledge differences in perspective, personal bias, and lack of awareness in some aspects of a concept which are more remote to one's experience. Concept maps have been shown to be core to efficient knowledge sharing ( 86 ), education, and enhanced problem solving ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concept maps, by putting individual mental models in the open, allow people to acknowledge differences in perspective, personal bias, and lack of awareness in some aspects of a concept which are more remote to one's experience. Concept maps have been shown to be core to efficient knowledge sharing ( 86 ), education, and enhanced problem solving ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of concept maps had been proved to enable them to focus on the most important information when making clinical decisions as well as helping to prioritize nursing interventions [14]. It has been suggested that concept mapping is successful in encouraging critical thinking by increasing students' active involvement with data organization, data comparison and correlation, and the integration of ideas [15,16]. Therefore, Kaddoura's study results can indirectly point out that critical thinking can help nursing students make effective clinical decisions.…”
Section: How Teaching Interventions Effect Cdmmentioning
confidence: 99%
“…Decreasing the organization complexity will also contribute to TKS [85]. From ICT perspective, knowledge map [95], [96] and concept map [97] are adopted to develop information systems. However, in [20] , the authors argued that ICT is a factor that leads to mismanagement of tacit knowledge.…”
Section: Policies and Approaches For Tksmentioning
confidence: 99%